Legal Protection for Cryptocurrency Investors: A Comparative Study of Indonesia and Singapore - Aulia, Fara; Sugiyono, Heru (Al-Risalah, 2026)
Crypto is digital money created through mining or issued by authorities, utilizing cryptography and blockchain for security. This study aims to analyze the legal protection framework for investors regarding the risks of cryptocurrency transactions, as well as the liability of service provider platforms, through a comparison between Indonesia and Singapore. The research method employed is a normative legal analysis using a statutory approach, a case-law approach, and a comparative approach. This study represents a novel contribution because no previous research has compared the concepts of investor protection and platform liability. Data sources include primary legal materials such as Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector, Law No. 8 of 1995 on the Capital Market, regulations of the Commodity Futures Trading Supervisory Agency, regulations of the Financial Services Authority, as well as Singaporean regulations such as the Payment Services Act 2019 and the Securities and Futures Act. The research findings indicate that Indonesia recognizes crypto assets as commodities, with oversight now transferred to the Financial Services Authority, and provides protection through Know Your Customer, Anti-Money Laundering, risk disclosure, and the Financial Sector Alternative Dispute Resolution Institution. However, there is no automatic compensation mechanism in place. Singapore has more comprehensive and proactive regulations to protect investors.